Mid-Regional Proadrenomedullin (MR-proADM) and Microcirculation in Monitoring Organ Dysfunction of Critical Care Patients With Infection: A Prospective Observational Pilot Study - Domizi, Roberta; Damiani, Elisa; Scorcella, Claudia; Carsetti, Andrea; Giaccaglia, Paolo; Casarotta, Erika; Montomoli, Jonathan; Gabbanelli, Vincenzo; Brugia, Marina; Moretti, Marco; Adrario, Erica; Donati, Abele (Frontiers in Medicine, 2021)
Introduction: Microvascular alterations are involved in the development of organ injury in critical care patients. Mid-regional proadrenomedullin (MR-proADM) may predict organ damage and its evolution. The main objective of this study was to assess the correlation between MR-proADM and Microvascular Flow Index (MFI) in a small cohort of 20 adult critical care patients diagnosed with infection, sepsis or septic shock. Further objectives were to evaluate the correlation between the clearance of MR-proADM and the variables of microcirculation and between MR-proADM and the Sequential Organ Failure Assessment (SOFA) score. Materials and methods: Prospective observational pilot study. Inclusion criteria: consecutive adult patients admitted to Intensive Care Unit (ICU) for or with infection-related illness. Daily measurement of MR-proADM and calculation of SOFA score, from admission in ICU to day 5. Repeated evaluations of sublingual microcirculation, collection of clinical data and laboratory tests. Results. Primary outcome: MR-proADM was not significantly correlated to Microvascular Flow Index (MFI) at admission in ICU. A clearance of MR-proADM of 20% or more in the first 24hours was related to the improvement of MFIs and MFIt (Percentual variation of MFIs +12.35 [6.01-14.59]% versus +2.23 [-4.45-6.01]%, p=0.005; MFIt + 9.09 [4.53-16.26] % versus –1.43 [-4.36-3.12] % p=0.002). Conclusion. The study did not support a direct correlation of MR-proADM with MFI at admission in ICU; however, it showed a good correlation between the clearance of MR-proADM, MFI and other microvascular variables. The study also supported the prognostic value of the marker. Adequately powered studies should be performed to confirm the findings.